2011
DOI: 10.1002/aqc.1212
|View full text |Cite
|
Sign up to set email alerts
|

A botanical classification of standing waters in Serbia and its application to conservation

Abstract: ABSTRACT1. The aim of this study was to describe a botanical classification for lakes in Serbia based on vegetation assemblage, basic water quality parameters and geographic region.2. Between 2008 and 2010 records from more than 1000 relevés were collated into one dataset. All relevés were derived from synoptic syntaxon tables .3. In order to fill geographical and methodological gaps in the database, additional field research was carried out during 2008, 2009 and 2010 at 18 new locations, producing a final tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…We showed that the diverse lake types of the Pannon Ecoregion were important for the conservation of freshwater biodiversity, harbouring a high number of macrophyte species (Lukács et al, 2009;Radulovič et al, 2011). Our results support the importance of small lakes and artificial lakes in the conservation of macrophyte diversity compared to large and natural lakes as it was confirmed by the high diversity of both submersed and emergent species.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…We showed that the diverse lake types of the Pannon Ecoregion were important for the conservation of freshwater biodiversity, harbouring a high number of macrophyte species (Lukács et al, 2009;Radulovič et al, 2011). Our results support the importance of small lakes and artificial lakes in the conservation of macrophyte diversity compared to large and natural lakes as it was confirmed by the high diversity of both submersed and emergent species.…”
Section: Resultssupporting
confidence: 72%
“…The Pannon Ecoregion contains some unique standing water habitat types, which are rare (or missing) in other European regions. For example, many standing waters in the ecoregion have a peculiar astatic character (temporarily dried out) which is attributed to the arid continental climate (Szesztay, 1974;Horváth et al, 2013;Radulovič et al, 2011). The climatic, geomorphologic and hydrologic features of standing waters resulted in a variety of lake types with well-developed submerged and emergent macrophyte vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…Natural standing waters are of glacial origin and they are distributed across almost the whole altitudinal gradient but dominate at higher elevations, while artificial ponds prevail at lower altitudes. Natural water bodies in lower and moderate altitudes such as river oxbows or shallow temporary ponds usually show higher macrophyte diversity [19,20] than oligotrophic lakes at high-altitude [7]. In addition, artificial ponds are often considered species-poor habitats [21].…”
Section: Introductionmentioning
confidence: 99%
“…Research on the relationships between lake hydromorphology and biology is an area of continuing growth and development, and one in which the CEN standards have a role to play. For example, in Scotland work is under way to link datasets on macrophytes and LHS, and similar work on building a database for LHS, macrophytes, and invertebrates is under construction in Poland, and in Serbia at the University of Novi Sad (Laketić, Radulović, Živković, Jurca, & Alford, ; Radulović, Laketić, & Teodorović, ).…”
Section: Applications Of the Cen Standardsmentioning
confidence: 99%